Ingestive Behavior of Young Lambs on Contrasting Tropical Grass Sward Heights - Silva, Joseane Anjos da; Poli, Cesar Henrique Espirito Candal; Tontini, Jalise Fabíola; Irigoyen, Lívia Raymundo; Modesto, Elisa Cristina; Villalba, Juan Jose (Frontiers in Veterinary Science, 2020)
The efficiency of grazing ruminant production systems is directly associated to the animals' ingestive behavior, and to structural characteristics of the pastures. The objective of this study was to evaluate the ingestive behavior of young lambs grazing three different heights of Capim Aruana (Panicum maximum). The experiment was carried out in two consecutive years, in which 30 tester lambs (4-5 months old) were equally divided into three paddocks (treatments) corresponding to different average sward heights of Aruana grass: (1) Tall-75 cm; (2) Medium-50 cm; and (3) Short-25 cm in a randomized block design. Ingestive behavior assessments were carried out every 28 days through 10-min observations of the main activities of the animals (grazing, ruminating, idling) and biting rate, from sunrise to sunset. In addition, the productive and qualitative characteristics of the pastures were assessed. Despite differences in pasture structure, grazing time (GT) and idling time were similar among treatments (P= 0.4266 and P= 0.2939, respectively). The shortest ruminating time (RT, P= 0.0181) was recorded in the treatment of lowest sward height. Lambs grazing on this treatment also showed 23% more bites per minute (P= <.0001) than animals in the Tall and Medium treatments. A Decision Tree analysis was performed for GT, identifying in a hierarchical order that the initial weight of the animals and sward height explained 62% (R² = 0.621) of the variation, representing the variables with the greatest influence on GT. Initial body weight explained 48% of the model. Thus, our research shows that the different sward heights of Capim Aruana mainly alter the lamb’s RT and biting rate, and that the animals’ initial body weight is a key factor influencing GT, given that this variable makes lambs more susceptible to changes in sward height.